THE RECONSTRUCTION OF ISLAMIC THEOLOGY IN THE UNITY OF SCIENCES - Yusriyah Yusriyah (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2015)
As a result of the processes of thinking on theological concept, Islamic theology may change according to its social dynamics. In the contemporary, theology can be studied by interdisciplinary sciences, which eventually theology became the source of the birth of some sciences. Hence, the science produced by the understanding of monotheism will produce peaceful religion for the universe (raḥmatan li ’l-‘ālamīn). The data presented in this article derived from the study applying literature review on the related topics of writing. Applying qualitative approach, this article showed that religion and science have a point of tangency. Science helps to facilitate human beings in their religious living. Concerning to faith, science activities can strengthen the faith and arise the motivation to express something in recognizing more toward God as the center of unity of existence (tawḥīd). In order to integrate the belief and sciences, it is needed the effort of islamization of science and the effort to reconstruct theology into a format that make it possible to dialogue with the reality of current development of thinking.